Formation of a Stable Positive Motivation to Study with Senior Students of Higher Military Educational Institutions by Creating a High Loyalty Atmosphere - Grafeeva, Ch. V. (2020)
The research relevance is connected with the fact that in domestic historiography the methodological problem of ways to overcome learning difficulties, associated with the lack of positive internal motivation, has not been practically studied with aspect of teaching English to students of military higher educational institutions. In foreign historiography, the issues of motivation formation under certain educational conditions are considered quite widely, however, without emphasis on the specifics of specialization of military higher educational institutions. The purpose of the article is to present the results of an empirical study conducted at the Military Medical Academy. The objectives of the article are to identify the actual motivation level to learn English among senior students of the Military Medical Academy; presentation of the main aspects in the methodology of creating a high loyalty atmosphere in English classes for senior students of the Military Medical Academy; consideration of further prospects for studies of the correlation between the high loyalty atmosphere and the sustainable positive motivation the formation for teaching English to students of the Military Medical Academy. The author of the article used the following methods: the content analysis of scientific literature, the method of pedagogical observation, statistical data analysis, as well as the method of sociological survey (questionnaire). The author of the article verified the scientific hypothesis of the study through the experiment on the basis of the Military Medical Academy (Moscow). In the experimental part of the study, elements of the high loyalty atmosphere were tested to form a positive internal motivation among senior students of the Military Medical Academy. During the experiment, the author of the article managed to bring out the high efficiency of the proposed methodology for teaching a foreign language by the example of training students in a military university.